Low-consumption and environment-friendly purification process of hypophosphorous acid

CN120681735BActive Publication Date: 2026-11-03HUBEI SINOPHORUS ELECTRONIC MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510985140.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-17
Publication Date
2026-11-03
Estimated Expiration
2045-07-17

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application discloses a low-consumption environment-friendly hypophosphite purification process and belongs to the technical field of hypophosphite purification. The application discloses a low-consumption environment-friendly hypophosphite purification process and belongs to the technical field of hypophosphite purification. The application discloses a low-consumption environment-friendly hypophosphite purification process and belongs to the technical field of hypophosphite purification. The application discloses a low-consumption environment-friendly hypophosphite purification process and belongs to the technical field of hypophosphite purification. The application discloses a low-consumption environment-friendly hypophosphite purification process and belongs to the technical field of hypophosphite purification. The application discloses a low-consumption environment-friendly hypophosphite purification process and belongs to the technical field of hypophosphite purification. The application discloses a low-consumption environment-friendly hypophosphite purification process and belongs to the technical field of hypophosphite purification. The application discloses a low-consumption environment-friendly hypophosphite purification process and belongs to the technical field of hypophosphite purification. The application discloses a low-consumption environment-friendly hypophosphite purification process and belongs to the technical field of hypophosphite purification. The application discloses a low-consumption environment-friendly hypophosphite purification process and belongs to the technical field of hypophosphite purification. The application discloses a low-consumption environment-friendly hypophosphite purification process and belongs to the technical field of hypophosphite purification. The application discloses a low-consumption environment-friendly hypophosphite purification process and belongs to the technical field of hyp phosphite purification. The application discloses a low-consumption environment-friendly hypophosphite
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a purification process for sodium hypophosphite, specifically a process involving drug chelation, crystallization, and resin purification to achieve the purification of sodium hypophosphite. Background Technology

[0002] Hypophosphite has strong reducing properties and is commonly used in meat products as a preservative and antioxidant, replacing nitrite. It is also used in the electronics industry as a raw material for capacitor-grade electrolytes; in electroless nickel plating as a reducing agent and polyamide catalyst; and in biological research and the pharmaceutical industry. The hypophosphite mentioned in this invention is any one of sodium hypophosphite, calcium hypophosphite, and ammonium hypophosphite.

[0003] The production process of hypophosphite is highly polluting, and some companies have had to shut down or withdraw from the market due to failure to meet environmental standards. On the demand side, due to the backward technology in China's hypophosphite industry, companies are not very enthusiastic about technological development. As a result, the quality of hypophosphite products has always been at a low to medium level, which cannot meet the needs of downstream industries such as food, pharmaceuticals, and electronics.

[0004] Currently, common purification methods for hypophosphite include crystallization, ion exchange, and precipitation. Crystallization utilizes the difference in solubility and crystallization characteristics between hypophosphite and phosphite to efficiently separate phosphite impurities. However, it is difficult to separate and remove metallic impurities in hypophosphite in compound form, such as iron hypophosphite and barium hypophosphite. Ion exchange can efficiently remove both metallic and anionic impurities from hypophosphite, but ion exchange resins are expensive, and most have weak regeneration capabilities. Hypophosphite production introduces a large amount of SO4. 2- Ions, for SO4 2- For ions, a common removal method is to add Ba salt to form Ba salt precipitate, but this method introduces a small amount of Ba. 2+ Ionic impurities. Summary of the Invention

[0005] One of the objectives of this invention is to overcome the shortcomings of the above-mentioned purification schemes and provide a low-consumption and environmentally friendly hypophosphite purification process. This purification process has less pollution, higher raw material utilization, is easy to operate and produce on a large scale, and the purity of the obtained product can reach the electronic grade.

[0006] The present invention discloses a low-consumption and environmentally friendly hypophosphite purification process, comprising the following steps: S1. Mix hypophosphite raw material powder with ultrapure water and heat to dissolve. Then filter out particulate impurities using a microfiltration membrane. S2. Add an appropriate amount of chelating agent to the filtrate obtained in step S1, stir evenly, and then transfer it to a dynamic crystallization kettle for slow cooling and crystallization. S3. Release hypophosphite crystals and mother liquor from the bottom of the crystallization reactor. After separating the hypophosphite mother liquor from the crystals, dry the hypophosphite crystals. S4. The hypophosphite mother liquor is processed through a macroporous adsorption resin to remove chelates from the mother liquor, and then reused in the crystallization process of a new batch of materials.

[0007] Preferably, the hypophosphite includes any one of sodium hypophosphite, calcium hypophosphite, and ammonium hypophosphite.

[0008] The raw material is industrial-grade hypophosphite with a purity of 95.5-99.5%. The metal impurities mainly include metals such as Fe, Ba, Cu, Mg, Ag, Al, Zn, Pb, Cd, Cr, and Co, with a total content of approximately 15 ppm. These metal impurities mainly originate from precipitation in the hypophosphite production unit and metal impurities carried in the raw material yellow phosphorus.

[0009] Preferably, in step S1, the mixing ratio of hypophosphite powder to ultrapure water is 2:0.5-1.5, and the mixture is heated and stirred until completely dissolved.

[0010] Preferably, the microfiltration membrane in step S1 is made of one of HEPE, PA, PTFE, or PS. The filtration accuracy of the microfiltration membrane is 0.1 μm to 1.0 μm.

[0011] The filtration precision of the microfiltration membrane mentioned in step S1 is 0.1μm, 0.2μm, 0.5μm, and 1.0μm.

[0012] Preferably, the filtration rate of the microfiltration membrane in step S1 is 8-15 m / h.

[0013] Some metallic impurities combine with phosphate ions to form hypophosphites, such as barium hypophosphite and zinc hypophosphite. These hypophosphites have low solubility and preferentially form crystal precipitates during cooling crystallization. They then mix with the product and are difficult to separate. Therefore, a suitable chelating agent is added to the hypophosphite solution before crystallization to form soluble chelates with the metallic impurities. Crystallization then proceeds, enriching the metallic impurities in the mother liquor as chelates. Different chelating agents exhibit varying selectivity for different metallic impurities. For example, trisodium ethylenediaminedisuccinate, ethylenediaminedisuccinic acid, and ethylenediaminetriacetic acid preferentially chelate transition metal ions such as Fe and Cu; polyvinyl alcohol, N,N,N-tris(carboxymethyl)ethylenediamine preferentially form stable complexes with Cu, Zn, Ni, and other metal ions; and ethylenediaminetetraacetic acid-based chelating agents preferentially combine with Mg and Ba to form stable chelates.

[0014] Preferably, the chelating agent added to the filtrate in step S2 is two or three of the following: trisodium ethylenediaminedisuccinate, ethylenediaminedisuccinic acid, ethylenediaminetriacetic acid, sodium hexametaphosphate, tris(2-carboxyethyl)phosphine, trisodium methylglycine diacetate, sodium diethyldithiocarbamate, silver diethyldithiocarbamate, polyvinyl alcohol, N,N,N-tris(carboxymethyl)ethylenediamine, disodium ethylenediaminetetraacetate, and ethylenediaminetetraacetic acid.

[0015] The amount of chelating agent added is 0.01-1‰ of the total mass of the sodium hypophosphite solution.

[0016] In the preferred S2, the cooling rate of the hypophosphite solution in the crystallization reactor is 10-20℃ / h.

[0017] In the preferred S2, during the crystallization process of the hypophosphite solution in the crystallization reactor, the stirring speed of the agitator is 70-150 rpm.

[0018] Preferably, the temperature set for heating and drying in the vacuum drying oven is 30-55℃.

[0019] Preferably, the product after the drying process described in step S3 is vacuum packaged and stored.

[0020] The macroporous adsorption resin is a non-ionic macroporous adsorption resin, which includes any two or more combinations of Zhengguang HOSD11, Zhengguang HOSD9, DuPont XAD3, DuPont XAD4, Hisilicon XAD2, Hisilicon HPD400, and Hisilicon HPD700Z.

[0021] The aforementioned combination refers to the combination obtained by filling resin columns with any one of the following: Zhengguang HOSD11, Zhengguang HOSD9, DuPont XAD4, DuPont AB-8, Hisilicon XAD2, Hisilicon HPD400, and Hisilicon HPD700Z, and then connecting them in series.

[0022] The researchers of this invention conducted screening tests on the resins. In the mother liquor after crystallization, metal ion impurities combined with chelating agents to form chelates. Some chelates have large molecular weights, resulting in poor adsorption effects on resins with such ionic impurities. Gel-type resins have small pore sizes, which easily lead to gel pore blockage and severely reduce the resin's lifespan. Through screening, it was found that the non-ionic macroporous network structure resin of this application can effectively adsorb organic impurities in the mother liquor and efficiently remove metal impurities from the mother liquor.

[0023] Preferably, the macroporous adsorption resin has an average pore size of 6.0-25.0 nm.

[0024] Preferably, the regenerator used in the regeneration process of the macroporous adsorption resin described in step S4 is one or two of sulfuric acid, phosphoric acid, hydrochloric acid, anhydrous ethanol, and sodium hydroxide.

[0025] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) This invention provides a low-consumption and environmentally friendly hypophosphite purification process. By utilizing the selectivity of chelating agents for metal ions, a suitable chelating agent is added before crystallization to avoid some metal impurities participating in the hypophosphite crystallization process and improve the crystallization and purification effect.

[0026] (2) This invention provides a low-consumption and environmentally friendly hypophosphite purification process. Compared with existing crystallization purification technology, this process can effectively remove metal ions from hypophosphite, and the reuse of crystallization mother liquor improves the utilization rate of raw materials and saves costs.

[0027] (3) This invention provides a low-consumption and environmentally friendly hypophosphite purification process. Previously, this technology was not available in the chemical industry. The proposal of this process is of great significance to the capacitor industry, electronic chemical industry, biological research and pharmaceutical industry.

[0028] (4) The purification process of hypophosphite does not require high-energy-consuming methods such as distillation. The technical solution of the present invention is purified by conventional reagent treatment, which has the technical effect of low energy consumption. Detailed Implementation

[0029] The technical solution of the present invention will be further described and illustrated below through examples. All raw materials used in the examples are commercially available or prepared using conventional methods.

[0030] Example 1 (1) Industrial grade sodium hypophosphite (purity ≥ 99.5%, metal ion content is shown in raw material-1 in Table 1) is mixed with ultrapure water at a ratio of 2:1.2, heated and stirred until completely dissolved, and the sodium hypophosphite solution is purified by using a 0.2μm HDPE microporous pleated filter to remove large particulate impurities in the solution.

[0031] (2) After adding 0.02‰ sodium hexametaphosphate and 0.1‰ trisodium ethylenediamine disuccinate as chelating agents to the sodium hypophosphite solution, the material is transported to the crystallization reactor for cooling and crystallization.

[0032] (3) The cooling rate inside the crystallization vessel was 10℃ / h. After slowly cooling to 0℃, the temperature was maintained for 1 hour. The sodium hypophosphite crystals and mother liquor were then discharged from the bottom of the crystallization reactor and transported to a centrifuge for washing and drying. Afterward, the crystals were dried at a constant temperature of 35℃ in a vacuum drying oven and then vacuum packaged for storage. The effective component of the dried sodium hypophosphite was 99.9wt%, the crystallization yield was about 43%, and the metal ion content is shown in Product-1 in Table 1.

[0033] (4) The crystallization mother liquor was purified by passing it sequentially through a primary resin column filled with Zhengguang HOSD11 and a secondary resin column filled with Zhengguang HOSD9 at a flow rate of 5 BV / h. When the flow rate of the primary resin column reached 200 BV, the resin was replaced. When the flow rate of the secondary resin column reached 350 BV, the resin was replaced. The metal content in the mother liquor after resin purification is shown in Mother Liquor-1 in Table 1.

[0034] (5) After soaking the replaced resin in 25wt% hydrochloric acid for 24 hours, rinse the soaked old resin column with 10wt% hydrochloric acid at a flow rate of 1BV / h, and finally rinse with ultrapure water to complete the resin regeneration.

[0035] Example 2 (1) The raw materials and specific operating steps are the same as those in (1) of Example 1, except that the filter element is replaced with an HDPE microporous pleated filter element with a filtration accuracy of 0.1μm. The metal content in the raw materials is shown in Raw Material-2 in Table 1.

[0036] (2) The specific operation steps are the same as those in (2) of Example 1, except that the chelating agent is replaced with 0.2‰ N,N,N-tris(carboxymethyl)ethylenediamine and 0.08‰ sodium diethyldithiocarbamate.

[0037] (3) The specific operation steps are the same as (3) in Example 1. The content of crystal metal ions is shown in Product-2 in Table 1.

[0038] (4) The specific operation steps are the same as (4) in Example 1, except that the primary resin is replaced with Hisilicon XAD-2 and the secondary resin is replaced with Hisilicon HPD400. The metal content in the mother liquor after resin purification is shown in Table 1 Mother Liquor-2.

[0039] (5) The specific operation steps are the same as (5) in Example 1.

[0040] Comparative Example 1 (1) The raw materials and specific operating steps are the same as those in (1) of Example 1.

[0041] (2) The specific operation steps are the same as those in (2) of Example 1, except that the chelating agent is replaced with 0.2‰ aminotrimethylene phosphate disodium and 0.02‰ ethylenediaminetetramethylenephosphonate sodium.

[0042] (3) The specific operation steps are the same as (3) in Example 1. The content of crystal metal ions is shown in Product-3 in Table 1.

[0043] (4) The specific operation steps are the same as (4) in Example 1. The metal content in the mother liquor after resin purification is shown in Table 1, Mother Liquor-3.

[0044] (5) The specific operation steps are the same as (5) in Example 1.

[0045] Comparative Example 2 The specific operating steps (1), (2), and (3) are the same as those in Example 1 (1), (2), and (3). The content of crystal metal ions is shown in Product-4 in Table 1.

[0046] (4) The specific operation steps are the same as (4) in Example 1, except that the primary resin is replaced with DuPont XAD16 and the resin filled in the secondary resin column is DuPont XAD1180.

[0047] The metal content in the mother liquor after resin purification is shown in Table 1, Mother Liquor-4.

[0048] (5) The specific operation steps are the same as (5) in Example 1.

[0049] Comparative Example 3 (1) Industrial grade sodium hypophosphite (same batch as in Example (1)) and sodium hypophosphite mother liquor that has been reused 4 times are mixed at a ratio of 1:1.4, heated and stirred until completely dissolved, and the sodium hypophosphite solution is purified by using a 0.2μm HDPE microporous pleated filter to remove large particulate impurities from the solution.

[0050] The specific operation steps (2), (3), (4), and (5) are the same as those in (2), (3), (4), and (5) of Example 1. The metal ion content of sodium hypophosphite crystals is shown in Product-5 in Table 1. The metal content of the mother liquor after resin purification is shown in Mother Liquor-5 in Table 1.

[0051] Table 1. Metal ion content in raw materials, products and mother liquor

[0052] In Table 1, the total metal content of Products 1 and 2 is <50 ppb, while the K, Ag, and Al content in Product 3 is relatively high. This indicates that the chelating agents used in Comparative Example 1, sodium aminotrimethylene phosphate and sodium ethylenediaminetetramethylenephosphonate, have poor selectivity for these three metal impurities, resulting in higher levels of some metals in the crystalline products. Chelating agents exhibit a certain degree of selectivity when adsorbing metal ions; therefore, appropriate chelating agents must be selected and combined to effectively adsorb metal ions in the solution.

[0053] Comparing the crystalline products of Example 1 and Comparative Example 2, it can be seen that DuPont XAD16 and DuPont XAD1180 have poor adsorption effects on sodium hexametaphosphate and trisodium ethylenediamine disuccinate. This is because chelating agents of different molecular weights have large differences in molecular size, and the resin has a certain selectivity in adsorbing chelating agents due to the different molecular sizes of the chelates. In the purification process of the crystallization mother liquor, it is necessary to select a macroporous adsorption resin with a suitable pore size according to the molecular weight of the chelating agent.

[0054] When the mother liquor is reused up to the 5th time, the crystallization and purification effect is poor due to the high enrichment of some metal impurities. Therefore, the mother liquor can be reused 4 times in this process.

[0055] Example 3 (1) Industrial grade sodium hypophosphite (purity 95.5%, metal ion content is shown in Table 2 Industrial Raw Materials-2) was used as raw material and mixed with ultrapure water at a ratio of 2:0.6. The mixture was heated and stirred until completely dissolved. The sodium hypophosphite solution was purified using a 0.5μm HDPE microporous pleated filter to remove large particulate impurities from the solution.

[0056] (2) After adding 0.05‰ of chelating agent hypophosphite and 0.2‰ of disodium ethylenediaminetetraacetate to the sodium hypophosphite solution, the material is transported to the crystallization reactor for cooling and crystallization.

[0057] (3) The cooling rate inside the crystallization vessel was 20℃ / h. After slowly cooling to -5℃, the temperature was maintained for 1 hour. The sodium hypophosphite crystals and mother liquor were then discharged from the bottom of the crystallization reactor and transported to a centrifuge for washing and drying. Afterward, the crystals were dried at a constant temperature of 55℃ in a vacuum drying oven and then vacuum packaged for storage. The effective component of the dried sodium hypophosphite was 99.9wt%, and the crystallization yield was approximately 60%. The metal ion content of the crystals is shown in Product-6 in Table 2.

[0058] (4) The crystallization mother liquor was purified by passing it sequentially through a primary resin column filled with DuPont XAD-4 and a secondary resin column filled with DuPont AB-8 at a flow rate of 5 BV / h. When the flow rate of the primary resin column reached 150 BV, the resin was replaced. When the flow rate of the secondary resin column reached 280 BV, the resin was replaced. The metal content in the mother liquor after resin purification is shown in Table 2, Mother Liquor-6.

[0059] (5) After soaking the replaced resin in anhydrous ethanol for 24 hours, rinse the soaked old resin column with anhydrous ethanol at a flow rate of 1 BV / h, and finally rinse with ultrapure water to complete the resin regeneration.

[0060] Comparative Example 4 (1) The specific operation steps are the same as (1) in Implementation Case 3, except that the filter element is changed to a 3.0μm HDPE microporous pleated filter element.

[0061] The specific operation steps (2), (3), (4), and (5) are the same as those in (2), (3), (4), and (5) of Example 3. The metal ion content of sodium hypophosphite crystals is shown in Product-7 in Table 2. The metal content in the mother liquor after resin purification is shown in Mother Liquor-7 in Table 2.

[0062] Comparative Example 5 (1) The specific operation steps are the same as (1) in Example 3.

[0063] (2) Sodium hypophosphite solution is directly fed into the crystallization reactor.

[0064] (3) The specific operation steps are the same as (3) in Example 3. The metal ion content of the crystallized product is shown in Product-8 in Table 2, and the metal ion content of the mother liquor is shown in Mother Liquor-8 in Table 2.

[0065] Table 2. Metal ion content in raw materials, products and mother liquor

[0066] After the hypophosphite is completely dissolved, some sparingly soluble or insoluble impurities in the raw material remain suspended in the hypophosphite solution. These particulate impurities are removed by selecting a suitable microfiltration membrane. As shown in Table 2, selecting a suitable microporous pleated filter cartridge to remove particulate impurities in the solution can effectively reduce the metal content in the crystalline product and mother liquor. Furthermore, adding a chelating agent to the solution before crystallization to form chelates with metal ions in the solution prevents some metal impurities from participating in the phosphate crystallization process, effectively reducing the content of metal ions such as Fe, Cu, Ba, and K in the product and mother liquor, which is beneficial for the reuse of the mother liquor.

[0067] Conclusion: In the purification process described in this invention, the selective complexation of some metal ions using chelating agents can improve the purification effect of the crystalline product. The mother liquor, after purification by macroporous resin adsorption, can be reused, improving raw material utilization. After the adsorption resin reaches saturation, desorption and regeneration restore the original adsorption capacity of the resin, achieving resin recycling, reducing application costs, and minimizing resource waste and environmental pollution. Furthermore, the hypophosphite purification technology mentioned in this invention has a simple process route, is easy to scale up for production, and has good market prospects.

Claims

1. A low-consumption and environmentally friendly hypophosphite purification process, characterized in that, Includes the following steps: S1. The hypophosphite raw material powder is mixed with ultrapure water and heated to dissolve. Then, the particulate impurities are filtered out using a microfiltration membrane. The hypophosphite includes any one of sodium hypophosphite, calcium hypophosphite, and ammonium hypophosphite. S2. After adding an appropriate amount of chelating agent to the filtrate obtained in step S1 and stirring evenly, the filtrate is transferred to a dynamic crystallization vessel and slowly cooled for crystallization. The chelating agent added to the filtrate includes two or three of the following: trisodium ethylenediaminedisuccinate, ethylenediaminedisuccinic acid, ethylenetriacetic acid, sodium hexametaphosphate, tris(2-carboxyethyl)phosphine, trisodium methylglycine diacetate, sodium diethyldithiocarbamate, silver diethyldithiocarbamate, polyvinyl alcohol, N,N,N-tris(carboxymethyl)ethylenediamine, and disodium ethylenediaminetetraacetate. S3. Release hypophosphite crystals and mother liquor from the bottom of the crystallization reactor. After separating the hypophosphite crystals from the mother liquor, dry the hypophosphite crystals. S4. The hypophosphite mother liquor is treated with a macroporous adsorption resin to remove chelates, and then reused in the crystallization process of a new batch of materials. The macroporous adsorption resin is a non-ionic macroporous adsorption resin, which includes any two or more combinations of Zhengguang HOSD11, Zhengguang HOSD9, DuPont XAD3, DuPont XAD4, Hisilicon XAD2, Hisilicon HPD400, and Hisilicon HPD700Z. The average pore size of the macroporous adsorption resin is 6.0-25.0 nm.

2. The low-consumption and environmentally friendly hypophosphite purification process according to claim 1, characterized in that, The raw material in S1 is industrial-grade hypophosphite with a purity of 95.5-99.5%; the mixing ratio of hypophosphite powder and ultrapure water is 2:0.5-1.

5.

3. The low-consumption and environmentally friendly hypophosphite purification process according to claim 1, characterized in that, The microfiltration membrane described in S1 is made of one of HEPE, PA, PTFE or PS.

4. The low-consumption and environmentally friendly hypophosphite purification process according to claim 1, characterized in that, The microfiltration membrane described in S1 has a filtration accuracy of 0.1μm, 0.2μm, 0.5μm or 1.0μm, and a filtration rate of 8-15m / h.

5. The low-consumption and environmentally friendly hypophosphite purification process according to claim 1, characterized in that, In step S2, the hypophosphite solution is cooled at a rate of 10-20℃ / h in the crystallization reactor.

6. The low-consumption and environmentally friendly hypophosphite purification process according to claim 1, characterized in that, In step S3, during the crystallization process of the hypophosphite solution in the crystallization reactor, the stirring speed of the agitator is 70-150 rpm.

7. The low-consumption and environmentally friendly hypophosphite purification process according to claim 1, characterized in that, In S3, the crystallization termination temperature of the hypophosphite solution in the crystallization reactor is -5 to -2℃.

Citation Information

Patent Citations

  • Industrial production method of electronic pure ammonium sulfite

    CN115353121A

  • A process for the purification of an alkali metal hypophosphite solution containing alkali metal phosphite

    GB827578A